Reconceptualizing Poor Leadership Through Islamic Lens: Conceptual Analysis, Pathogenesis and Systemic Consequences in the Qur’ān - Mohamed Bile Hashi; Ahmed-Nor Mohamed Abdi (Journal of Islamic Thought and Civilization, 2026)
Academic discourse on leadership has traditionally focused on good leadership, while insufficient attention has been paid to poor leadership, particularly within Islamic academic frameworks. This neglect is problematic given the correlation between poor leadership and systemic governance failures, societal fragmentation, and institutional corruption. The present study addresses this gap by developing a theologically grounded Islamic conceptualization of bad leadership, employing qualitative, literature-based analysis. It integrates thematic analysis of Qurʾānic verses on leadership failures (e.g., ẓulm [oppression], kibr [arrogance], khiyānah [betrayal of trust]) and classical exegeses (Tafsīr Mustafa Khattab, Ibn Kathīr, Fī Ẓilāl al-Qurʾān). Additionally, it situates itself within contemporary Islamic scholarship and Western leadership theories (e.g., Lipman-Blumen, Kellerman) for comparative critique. The findings demonstrate that poor leadership in the Qurʾān is characterized by ẓulm (oppression), kibr (arrogance), and khiyānat al-amānah (betrayal of trust), as well as a rejection of shūrā (consultation) and divine accountability. The origins of bad leadership according to the Qurʾān include theological factors, psychological aspects, and moral-systemic issues. Poor leadership from an Islamic perspective affects individuals socially, spiritually, and institutionally. This study offers a systematic Islamic model to diagnose and mitigate bad leadership, bridging theological ethics with organizational practice. It provides faith-based tools for identifying and addressing bad leadership origins while proposing an integrative model that connects Islamic ethical theology with contemporary organizational leadership practice. The framework offers potential applications in leadership development, organizational ethics, and institutional reform within Muslim communities and beyond.